A Lower Bound on the Differential Entropy of Log-Concave Random Vectors with Applications - Arnaud Marsiglietti (Entropy, 2018)
We derive a lower bound on the differential entropy of a log-concave random variable X in terms of the p-th absolute moment of X. The new bound leads to a reverse entropy power inequality with an explicit constant, and to new bounds on the rate-distortion function and the channel capacity. Specifically, we study the rate-distortion function for log-concave sources and distortion measure